2008
DOI: 10.1158/1535-7163.mct-07-2063
|View full text |Cite
|
Sign up to set email alerts
|

A small-molecule inhibitor of Tcf/β-catenin signaling down-regulates PPARγ and PPARδ activities

Abstract: Activation of the Wnt/B-catenin signaling pathway occurs in several types of cancers and thus it is an attractive target for anticancer drug development. To identify compounds that inhibit this pathway, we screened a chemical library using a cell-based B-catenin/Tcf -responsive reporter. We identified FH535, a compound that suppresses both Wnt/B-catenin and peroxisome proliferator -activated receptor (PPAR) signaling. FH535 antagonizes both PPAR; and PPARD ligand -dependent activation and shows structural simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
144
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(153 citation statements)
references
References 45 publications
7
144
2
Order By: Relevance
“…PPARδ, a widely expressed transcriptional factor, was reported to be a downstream target of WNT/β-catenin signaling. 15,16 He et al 16 found that transfected CRC cells with a dnTCF-4 expression vector significantly suppressed the activity of PPARδ promoter, which suggested that PPARδ was regulated by β-catenin/TCF pathway. We found that activation of WNT/β-catenin signaling by SB216763 reversed the reduction in the PPARδ protein induced by CSE stimulation, which suggested PPARδ may be a downstream target of β-catenin signaling (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPARδ, a widely expressed transcriptional factor, was reported to be a downstream target of WNT/β-catenin signaling. 15,16 He et al 16 found that transfected CRC cells with a dnTCF-4 expression vector significantly suppressed the activity of PPARδ promoter, which suggested that PPARδ was regulated by β-catenin/TCF pathway. We found that activation of WNT/β-catenin signaling by SB216763 reversed the reduction in the PPARδ protein induced by CSE stimulation, which suggested PPARδ may be a downstream target of β-catenin signaling (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…15,16 PPARs are nuclear receptor/ligand-activated transcription factors, composed of three known isoforms: PPARα, PPARδ, and PPARγ. 17 PPARs regulate various cellular processes involving lipid metabolism, glucose homeostasis, and inflammation.…”
mentioning
confidence: 99%
“…If Wnt/-catenin activity is required for proliferation during this period, then inhibition or activation of the pathway prior to terminal mitosis should result in a reduction or enhancement in the number of proliferating cells, respectively. To test this hypothesis, we utilized an in vitro strategy in which cochlear explants were established at E12 and maintained in one of two different Wnt/-catenin inhibitors: FH535, a specific TCF inhibitor (Handeli and Simon, 2008), or IWR-1, which acts by stabilizing axin and subsequently increasing -catenin degradation . Conversely, some explants were maintained in LiCl, an agonist of Wnt/-catenin signaling that blocks the kinase activity of Gsk3, preventing -catenin degradation (Klein and Melton, 1996).…”
Section: Research Articlementioning
confidence: 99%
“…In addition, we indicate that Tcf-4 expression increases significantly with the ascending pathologic grade of gliomas and correlates positively with AKT1 expression. Since specific agents inhibiting β-catenin/Tcf-4 and AKT1 are available (26,27), our data provide the rationale for combining these inhibitors in treating specific forms of cancer, such as in a subset of glioma in which both β-catenin/Tcf-4 and AKT1 are activated.…”
Section: Discussionmentioning
confidence: 93%